Photonic Crystal Based 2/3/6- Way Optical Splitter and Demultiplexer - Goyal, Richa; Nayak, Banoj Kumar; Tulapurkar, Ashwin; Achanta, Venu Gopal (Frontiers in Physics, 2019)
We present 2-, 3-, and 6-way optical demultiplexer and optical filters based on coupled waveguide and photonic crystal cavities. Demultiplexers with 3 nm channel separation and optical filters with different transmission efficiencies are presented. The structures designed on GaAs wafers having the smallest footprint of 78 square micron are suitable for integrating all-optical devices for planar integrated circuits